Measures for clinical practice and research - Corcoran, Kevin; Fischer, Joel. (Oxford ; New York : Oxford University Press, 2013)
This essential resource has dozens of new scales as well as updated information for existing instruments, expanding and cementing its utility for members of all the helping professions, including psychology, social work, psychiatry, counseling, nursing, and medicine.
V. 1. Couples, families, and children -- v. 2. Adults.
Keywords: Psychological tests; Psychological Tests; Psychotherapy